English and Slang Adaptation on E-Commerce Platforms as an Implication for Students’ Digital Language Comprehension - Atik Muhimatun Asroriyah; Rosita Sofyaningrum; Muhammad As'ad (The Future of Education Journal, 2025)
This study explores how university students adapt to English and slang on e-commerce platforms and the implications for their digital language comprehension. The research focuses on understanding how students interpret informal expressions, abbreviations, and context-specific terminology commonly used in online marketplaces, reflecting their digital literacy and contemporary English competence. Utilizing a qualitative approach, data were collected through observations, interviews, and analysis of student interactions on e-commerce platforms. Findings indicate that frequent engagement with digital marketplaces enhances students’ ability to comprehend and use both standard and informal English forms, including slang, in contextually appropriate ways. This study highlights the importance of integrating digital language experiences into English learning, emphasizing that e-commerce environments can serve as a practical space for developing digital literacy and communication skills.